Edukasi Strategi Penjualan Produk Herbal di Desa Sei Limbat Kecamatan Selesai Kabupaten Deli Serdang Tahun 2023 - Heppy Nova Jayanti; Farah Dhiba (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2023)
A company engaged in selling various herbal products, various health products and herbal cosmetics. The purpose of this research is to determine efforts to increase sales through current and future marketing strategies to be more effective and achieve maximum profits. This research is field research with qualitative descriptive methods, data and information collected through interviews, observation and documentation. The factor causing the decline in sales and not achieving the desired target is an ineffective marketing strategy. So far the marketing strategy implemented has been quite good, namely by implementing advertising, sales promotions and personal selling. However, in practice these three elements do not work according to what the company expects due to a lack of evaluation of each element, so that the results achieved are not optimal. Therefore, you should add promotional activities that are relatively cheaper and more effective, namely through advertising with larger signage media and an annual calendar as well as carrying out a more in-depth evaluation of the marketing strategy being implemented, so that a goal can be achieved, namely increasing sales.